Evaluation of performance of dimethyl ether and high-pressure refrigerants under varied evaporating temperature - Mitrakusuma Windy H.; Setyawan Andriyanto; Simbolon Luga M. (BIO Web of Conferences)
Dimethyl ether is an organic compound that has the potential to be used as an environmentally friendly refrigerant. In this study, the performance of dimethyl ether refrigerant was tested and compared with other refrigerants having high working pressure, namely R410A, R410B, and R32. The study results show that dimethyl ether has a lower cooling capacity compared to R410A, R410B, and R32, in the order of 37% to 40%. However, the compression work of the cooling system with dimethyl ether is much lower, i.e., in the order of 30.7% to 36.9%. As a result, the coefficient of performance (COP) of the cooling machine with dimethyl ether is 7.4% to 10.6% higher than that of the three high-pressure refrigerants. The COP increases with the increase of evaporating temperature.